Civil Society in South-Eastern Europe and the Role of Greece in the Stability Pact - Kondonis, Haralambos (Études helléniques / Hellenic Studies, 2002)
Signed on June 10 1999, in Cologne as a European Union initiative, the Stability Pact for S/E Europe has had various effects on the Balkans. What remains to be seen is how a region with little experience in civil society will manage. Especially interesting will be the role of the NGO . In fact, the author discusses how Greece and Greek NGOs could play an important role in the Balkans.